Exploring the intricacies of plant growth promoting rhizobacteria interactions: an omics review - Mmotla, Kamogelo; Sibanyoni, Nompumelelo R.; Allie, Farhahna; Sitole, Lungile; Mafuna, Thendo; Mashabela, Manamele D.; Mhlongo, Msizi I. (Annals of microbiology, 2025)
Plant growth-promoting rhizobacteria (PGPR) are beneficial microorganisms that inhabit the rhizosphere. PGPR play a role in stimulating plant growth and development and enhancing plant resistance and tolerance to biotic and abiotic stresses. To effectively fulfil their roles, PGPR engage in intricate interactions with one another, a phenomenon that occurs within the rhizosphere. Understanding the modes of communication and molecular mechanisms underlying these interactions is crucial for harnessing their full potential, particularly in sustainable agriculture. By exploring transcriptomic and metabolomic alterations driven by these interactions, as well as the integration of advanced omics technologies, researchers can uncover new insights into decoding these complex processes, paving the way for innovative strategies to enhance sustainable agriculture.